Preliminary Model Development for Integration of Transportation and Logistic System - Rafi, Salahudin (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2023)
This study aimed to establish a measurement model for the seamless integration of transportation and logistics systems. The model was crafted by conducting a comprehensive literature review and validating the content with experts in the field. Subsequently, exploratory and confirmatory factor analysis was performed on data gathered from 80 participants within the transportation and logistics industry. As a result, the study revealed three fundamental dimensions that constitute integrating transportation and logistics systems: interconnectivity, sustainable innovation, and stakeholder collaboration. The initial results of this study are a foundation for future research with a more extensive sample size.